The Effects of on-call duties on cognitive functions in anaesthesia residents HUSM - Ahmad, Azila (2010)
INTRODUCTION Cognitive functions play a vital role in safe anaesthetic practice and there are various factors that affect the cognitive functions. OBJECTIVES The aim of this study is to determine the effects on cognitive functions in anesthesia residents doing on-call duty in HUSM and to compare between demographic factors and on-call features with cognitive functions. METHODOLOGY This study includes all the anesthesia residents in the Department of Anaesthesiology, HUSM after written informed consent was obtained. The data was collected from 1st January until 28th February 2010. Four cognitive tests were used in this study which were Mini Mental State Examination (MMSE), Stroop Color Word Test (SCWT), Concentration Test (CT) and Reaction Time Test (RTT). Other associated factors affected by on-call such as Stanford Sleepiness Scale (SSS), Busy Score (BS) and psychological Stress Score (PSY) were also recorded. RESULTS There was 45 respondents contributing in this study and majority were males (62.6%), Malays (77.8%) and married (77.8%). Most of the anaesthetist residents (82.2%) were in the middle age group (30-39 year-old) and they had working experiences in anaesthesia between 5-10 years (66.7%). The major type of on-call duty was ICU call (46.7%) and most of the on-call duties were as a medical officer (75.6%). There were 11.1% of the residents had no sleep at all during on-call and majority sleep less than 4 hours (75.6%). Most of the anaesthesia residents (60.0%) scored moderate in SSS (3-4) and PSY (4-6). Majority of them (62.2%) also scored BS as moderate (4-6). The relationship between the three groups score (SSS, PSY and BS) with various demographic data and on-call features were not significant (p>0.05). There were decreased in cognitive test post-call and was significantly difference in SCWT (p=0.011) and CT (p=0.001). However, there was no significant difference between various demographic data, on-call features and all three score groups (SSS, PSY and BS) with cognitive functions (p>0.05). There was a significant correlation between SSS with PSY group (p=0.001), SSS with BS group (p=O.Oll) and PSY with BS group (p=0.001). CONCLUSION We conclude that the cognitive functions of anaesthesia residents particularly in SCWT and CT were significantly altered after on-call duties.